Optimalisasi Kinerja BUMDes melalui Penerapan Good Corporate Governance untuk Keberlanjutan di Kecamatan Ngargoyoso Kabupaten Karanganyar - Rois, Dimas Ilham Nur; Raisa Aribatul Hamidah; Dheny Hendrawan (Politeknik Ganesha Medan, 2025)
This objective focuses on the application of good corporate governance to optimize BUMDes performance. BUMDes in the Ngargoyoso sub-district made up the study's population. Six BUMDes were collected as research samples through the use of purposive sampling. Data was obtained by observation and interviews. The research method used is qualitative research using triangulation analysis techniques. The results of this study indicate that the implementation of good corporate governance of BUMDes in Ngargoyoso District is good in the principles of responsibility, independence and firness. However, it is still not good in applying the principles of transparency and accountability. BUMDes always applies the precautionary principle in making decisions according to and not violating the rules. BUMDes management decisions are taken objectively without interference from parties with personal interests. BUMDes is open to community participation and nondiscrimination in recruitment. BUMDes still lacks in providing adequate information as a form of transparency in BUMDes management. The application of accountability is still weak in human resources owned by BUMDes, especially the treasurer. Treasurers still lack an understanding of the application of accounting according to standards because most treasurers are not accounting graduates. Optimization of BUMDes performance can be achieved through improved implementation of good corporate governance, which not only strengthens financial performance, but also BUMDes' contribution to inclusive and sustainable village development.